Protective effect of cerium oxide nanoparticle on sperm quality and oxidative damage in malathion-induced testicular toxicity in rats: An experimental study - Heresh Moridi; Seyed Abdolhakim Hosseini; Hossein Shateri; Nejat Kheiripour; Arastoo Kaki; Mahdi Hatami; Akram Ranjbaran (Shahid Sadoughi University of Medical Sciences, 2018)
Abstract Background: Malathion is an organophosphorus pesticide that commonly used in many agricultural and non-agricultural processes. Previous studies have reported the effects of melatonin on the reproductive system. Cerium dioxide nanoparticles (CeNPs) due to their antioxidative properties are promising to impact on the development of male infertility. Objective: The aim of this study was to evaluate the effect of CeNPs on oxidative stress and sperm parameters after malathion exposure of male rats. Materials and Methods: 36 adult male Wistar rats were divided into 6 groups (n=6/each): Control, CeNPs -treated control (15 and 30 mg/kg/day), malathion (100 mg/ kg/day), and CeNPs -treated malathion groups (15 and 30 mg/ kg/day). At the end of the study (4 wk), the sperm counts, motility, and viability in the testis of rats were measured, also lipid peroxidation, total antioxidant capacity, and total thiol groups in homogenate testis were investigated. Results: Malathion significantly reduced sperm count, viability, and motility than the control rats (p<0.001). Co-treatment of malathion with CeNPs 30 mg/kg had a protective effect on sperm counts (p=0.03), motility (p=0.01), and viability (p<0.001) compare to malathion group. Also, the results showed that malathion reduced testis total anti-oxidant capacity, the total thiol group, and increased testis malondialdehyde than the control rats (p<0.001). CeNPs 30 mg/kg are increased total antioxidant capacity (p<0.001) and total thiol group (p=0.03) compared to malathion group. CeNPs at both doses (15 and 30 mg/kg) improved malondialdehyde than the malathion group (p<0.001 and p=0.01 respectively). Conclusion: CeNPs 30 mg/kg administered considerably restored testicular changes induced by malathion. The improvement of oxidative stress by CeNPs may be associated with increased sperm counts, motility and viability in the testis.